Fitness of eventing horses submitted to interval training - Azevedo Gonçalves, J.; Kretzmann Filho, N. A.; Rodrigues, R.; Jadoski, W.; Beretta, B.; Bahi Aymone, A. C.; Pires Neves, A. (International Journal of Equine Science, 2022)
The fitness of eventing horses was assessed in field tests through the use of heart and respiratory rates and blood biochemical parameters. The first stage (S1) lasted three days and consisted of the following three tests: the incremental speed test (IST), the incremental jumping test (IJT), and the jumping course (JC). Following the first stage, horses were submitted to a six-week interval training program and were then submitted to another evaluation, the second stage (S2), of the same tests as in the first stage. Lower heart rate (HR) values were observed during the incremental speed test in S1 than in S2. The enzymes creatine kinase (CK), aspartate transferase (AST), and lactate dehydrogenase (LDH) showed significant speed-related reductions in the second stage in comparison with the first stage. HR increased significantly during the incremental jumping test in the upper obstacle heights (55 and 70 cm). Respiratory rate showed a significant decrease in the last two laps and at 10 min after exercise in the second stage, compared to the first stage. Values of LDH were lower in the second stage than in the first stage, and AST values were significantly lower at 55 cm and 10 min after exercise in S2. During the jumping course, RR had better recovery in the second stage than in the first stage, and glucose decreased during the course in both stages. The enzymes CK and AST presented higher levels at 10 min after exercise in the second stage than in the first stage. The field tests can be utilized for evaluating the fitness of eventing horses.